EFISIENSI PENGALIRAN JARINGAN IRIGASI MALAKA (STUDI KASUS DAERAH IRIGASI MALAKA KIRI) - Bunganaen, Wilhelmus; Ramang, Ruslan; Raya, Lucya L.M. (Jurnal Teknik Sipil, 2017)
Irrigation efficiency is defined as ratio between the total of water supplied is reduced water losses with the total supplied. Irrigation water losses that occurs during water supplying mainly caused by seepage in wet canal section, evaporation (generally insignificant) and operational losses dependent on irrigation water management system. The purposes of this research is to analyze the magnitude of the efficiency of Irrigation network in Malaka. This research is done on the primary, secondary and tertiary canal. The efficiency of Malaka irrigation network is analyzed by the method of water discharge in ? water discharge out. The data used in this analysis is the primary data such as flow rate data by current meter for primary and secondary canal and flow rate data by a float for tertiary canal. In addition to the primary data also used secondary data from the nearest Climatological Stasiun. The results of analysis, water losses caused by evaporation is very insignificant, so water losses is caused by physical canal factors with smallest water loss occurred at BBKi.1outflow-BBKi.2inflow canal is 3,541% and most of loss that occured at BNM.6outflow-BNM.7inflow canal is 0.066 m3/sec. The average efficiency of the whole network of irrigation at Malaka Kiri 84.371% with primary canal efficiency is 90.343%, and secondary canal efficiency is 82.878%.